Cross-listing flows under uncertainty: an international perspective - Agyemang A; Balli F; Gregory-Allen R; Balli HO (Taylor and Francis Group, 2024)
The impact of policy uncertainty on corporate decisions and strategies continues to receive significant interest in recent discussions. As a contribution, this study examines how economic policy uncertainty (EPU) in the domestic and global markets impacts corporate cross-listing decisions. To this end, we employ firm and country-level data from 1990 to 2016 from 13 countries. We implement a Granger Causality, Quantile on Quantile Regression (QQR), and Wavelet Coherence approaches and show that monthly local and global EPU influence the cross-listing decisions of firms, with stronger influence for firms from smaller domestic markets. We suggest that firms from smaller domestic markets seek more cross-listing in the face of high local EPU and reduce or avoid cross-listing during high global EPU periods. Our findings suggest that policy transparency could have important implications for current and future corporate decisions.
Keywords: Economic policy uncertainty; cross-listing; Granger Causality; Quantile on Quantile Regression; and Wavelet Coherence